Pengaruh Media Wordwall Terhadap Hasil Belajar Hiragana - Asnita, Mela; wikarya, Rahmi Oktayory (Universitas Negeri Padang, 2024)
This study is motivated by obstacles of students who tend to memorize vocabulary using romaji letters without seeing the letters. Memorize vocabulary using letters without looking at the hiragana letters. Hiragana and forget the hiragana learned previously, because the learning media previously used has not made students interested in remembering hiragana. The selection and use of media in learning needs to condition, students’ needs, and in according with the development of technology. Based on this research, the researchers will use one of the media technology related to educational media, namely a media platform called wordwall. The purpose of the study is to determine the effect of wordwall media on hiragana learning outcomes and students’ responses to use wordwall media. This research is a type of quasi-experimental research that uses a one-group pretest-posttest design. The research sample was a X MIPA 2 class students SMAS Adabiah Padang which amounted to 36 students. The results showed that the test result with paired sample t-test test significant value in the column sig. (2tailed) is 0,000, this is smaller than the significance level of 0,05. Thus, H0 is rejected which means that wordwall media has a impact on the student’s hiragana learning outcomes in class X MIPA SMAS Adabiah Padang. Then the results of questionnaire data regarding students responses to the application of wordwall media in learning hiragana shows an average value of 87. This mean that there is a significant effect of using wordwall media on hiragana learning outcomes.